SISTEM INFORMASI REKAM MEDIS PUSKESMAS JAYENGAN SURAKARTA - Supriyanto .; Sri Huning Anwariningsih; suryono . (Universitas Sahid Surakarta, 2012)
Service health in Puskesmas need the existence of support from various related/ relevant factor, one of them is well-held of medical record matching withstandard going into effect. Medical record represent legal document which contain stuffing which enough about patient identity, diagnosa, therapy and all that happened atpatient. And bind medical record also represent documentation network activity of medical service given by health institution to patient. Because medical record representthe part of the health system improved and either through medical and also judicially In this research of writer chosen Puskesmas Jayengan Surakarta as reseaarch place. Medical record information system take care of road street in this PuskesmasJayengan good for process medical record data of patient covering registration of patient, doctor data, officer data, medical record data This research aim to make efficient medical record information system and make its implementation in visual pemrograman language of basic 6.0. this formulawriting internal issue is how to make medical record information system in Puskesmas Jayengan ? Used by Methodologies writing is data method and method approach. Data writer method use like : bibliography, observation. Method approach of writer use like :analysis, scheme, test drive, implementation. From submitted/ sent writing can be taken by conclusion that existing implementation have earned to be used for the information system of medical record,but admit of to be developed for the data processing of other related to medical record information system.